Randomised trials relevant to mental health conducted in low and middle-income countries: protocol for a survey of studies published in 1991, 1995 and 2000 and assessment of their relevance - Duley Lelia (BMC Psychiatry, 2006)
Abstract Background A substantial proportion of the psychiatric burden of disease falls on the world's poorest nations. Despite this, relatively little is known about the quality and content of clinical research undertaken in these countries, or the relevance of the interventions evaluated and specifically that of randomised trials. This project aims to survey the content, quality and accessibility of a sample of trials relevant to mental health conducted within low and middle-income countries; to compare these with studies conducted in high-income countries; and to assess their relevance for the needs of low and middle-income countries. Methods An extensive search for all trials, or possible trials, published in 1991, 1995 and 2000 with participants in low and middle-income countries has already been conducted. Studies evaluating prevention or treatment of a mental health problem within these three years will be identified and further searches conducted to assess completeness of the initial search. Data on study quality and characteristics will be extracted from each report. Accessibility will be estimated based on whether each citation is available on MEDLINE. Trials relevant to schizophrenia will be compared with a random sample of schizophrenia trials from high-income countries in the same years. Topics covered by the trials will be compared with the estimated burden of disease. Conclusion Trials and systematic reviews of trials are the gold standard of evaluation of care and increasingly provide the basis for recommendations to clinicians, to providers of care and to policy makers. Results from this study will present the first assessment of the scope, quality and accessibility of mental health trials in low and middle-income countries.